Estymacja parametrów rozkładów w mieszance dwóch rozkładów Poissona - Kuźmiński, Łukasz; Nikodem, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
For a heterogeneous portfolio we assume that the number of claims has the Poisson distribution with a variable parameter λ. The claim intensity is the outcome of a mixing variable ʌ. Then the claim number distribution is the mixed Poisson distribution with a mixing parameter ʌ. Two estimation methods for the case of the mixture of two Poisson distributions will be com-pared in this paper: the maximum likelihood and the method of moments. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (19); 2007; nr 1180, s. 75-84